The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/odi.13662
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation is effective in oral lichen planus: A randomized, controlled, double‐blind study

Abstract: Oral lichen planus (OLP) is a chronic inflammatory mucocutaneous disease, affecting 1%-2% of the population at middle age, with a discrete female predominance (Anuradha et al., 2008;Gupta et al., 2013). OLP aetiology is unknown but evidence suggests that this disease is an immune-mediated process orchestrated by CD 4+ and CD 8+ T lymphocytes as well as by diverse inflammatory cytokines that lead to the apoptosis of epithelial cells (Kurago, 2016;Payeras et al., 2013).Reticular OLP represents the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 43 publications
(53 reference statements)
2
54
0
Order By: Relevance
“…Similar studies were conducted using PBM therapy with the aim of treating OLP [ 21 , 22 ]; however, there is no consent on the exact PBM dosimetry or treatment protocol for the management of erosive OLP. In this context, a randomized double-blind study by Rodrigues et al [ 23 ], showed that the use of PBM can be as effective as corticoid therapy in treating oral lichen planus with no adverse side effects noted. In their study, a 660 nm diode laser was used in a continuous mode with a spot size of 0.283 mm 2 , an output power of 100 mW with a 5 s of exposure time per point and 0.5 J of total energy per point twice a week for 4 weeks and for a total of eight sessions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies were conducted using PBM therapy with the aim of treating OLP [ 21 , 22 ]; however, there is no consent on the exact PBM dosimetry or treatment protocol for the management of erosive OLP. In this context, a randomized double-blind study by Rodrigues et al [ 23 ], showed that the use of PBM can be as effective as corticoid therapy in treating oral lichen planus with no adverse side effects noted. In their study, a 660 nm diode laser was used in a continuous mode with a spot size of 0.283 mm 2 , an output power of 100 mW with a 5 s of exposure time per point and 0.5 J of total energy per point twice a week for 4 weeks and for a total of eight sessions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a randomized double-blind study by Rodrigues et al [ 23 ], showed that the use of PBM can be as effective as corticoid therapy in treating oral lichen planus with no adverse side effects noted. In their study, a 660 nm diode laser was used in a continuous mode with a spot size of 0.283 mm 2 , an output power of 100 mW with a 5 s of exposure time per point and 0.5 J of total energy per point twice a week for 4 weeks and for a total of eight sessions [ 23 ]. A systematic review and meta-analysis by Wang et al [ 12 ] argues that although PBM is proving to be a reliable alternative to topical corticosteroids, additional long-term randomized clinical trials and well-designed RCTs with long-term periods are still recommended to consolidate the effectiveness of PBM [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the connection between OLP and HSV-1 remains unclear, the use of oral acyclovir in OLP patients has been shown to be beneficial. Aside from antiviral agents, some unexplored variables, such as probiotics [ 25 ] and photobiomodulation [ 26 ], should be considered in future clinical trials for OLP patients. This approach demonstrated promising results by modifying clinical and microbiological parameters in the oral environment that may also affect the response to OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical OLP symptoms were identified in terms of the modified criteria. Clinical and function scores of OLP individuals were evaluated according to the previous investigation 25 . Signed informed consents were received from participants.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical and function scores of OLP individuals were evaluated according to the previous investigation. 25 Signed informed consents were received from participants. All human studies were approved by the Institutional Ethical Committee of Shanxi Medical University.…”
Section: Methodsmentioning
confidence: 99%